Pengaruh Pengetahuan Keuangan, Perilaku Konsumtif, Kontrol Diri Terhadap Perilaku Pengelolaan Keuangan Pada Penggemar K-Pop di Jakarta - Irvan, Noormansyah; Fifi Febriyanti Putri (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the influence of financial knowledge, consumptive behavior, self-control influence financial management behavior. This research focused on K-Pop fans in Jakarta.This research is quantitative in nature. The method used in this study is descriptive verificative. The sampling method applied is non-probability sampling, characterized by purposive sampling. The study gathered 195 respondents as samples, with data collection conducted through questionnaires distributed via Google Form on social media. The data was processed using SPPS 23, with data analysis methods including data quality testing,stastical data analysis, classical assumption tests, multiple linear regression test, and hypothesis testing. The results of this study show that the variables of financial knowledge and consumptive behavior partially have a significant influence on financial management behavior. Meanwhile, the self-control variable, when tested partially, has no significant effect on financial management behavior.